Structural properties of bi-layer Molybdenum Thin-film deposited by RF magnetron sputtering for CZTS solar cells - Gupta A.A.K.S.; Ahamed E.M.K.I.; Quamruzzaman M.; Matin M.A.; Rahaman K.S.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adhesion; Compressive stress; Copper compounds; Crystallite size; IV-VI semiconductors; Layered semiconductors; Magnetron sputtering; Molybdenum; Oxidation; Sulfur compounds; Thin film solar cells; Tin compounds; Zinc sulfide; Bi-layer; Copper zinc tin sulfides; Photovoltaic applications; rf-Magnetron sputtering; Rf-sputtering; Structural studies; Thin Film Solar Cells (TFSCs); Vacuum thermal annealing; Thin films